Effects of Training and Coaching With Performance Feedback on Teachers' Use of Pyramid Model Practices. (November 2015) - Hemmeter, Mary Louise; Hardy, Jessica K.; Schnitz, Alana G.; Adams, Jessie Morris; Kinder, Kiersten A.
Training and coaching with performance feedback has been effective for supporting teachers to use evidence-based instructional practices. However, coaching with performance feedback has primarily been used to support teachers to use discrete skills, and there has been little evidence of maintenance and generalization. The purpose of this study was to examine the effects of a professional development intervention on teachers' implementation of practices related to the Pyramid Model for Promoting Social-Emotional Competence in Young Children, as well as the extent to which teachers generalized and maintained those practices. A multiple probe design across sets of Pyramid Model practices replicated across three teachers was used in this study. All teachers acquired the practices and maintained the practices after coaching ended. There was some evidence of generalization for all three teachers. The effects of teacher implementation on classroom-wide incidences of challenging behavior were mixed. Teachers all rated the coaching positively.